Turnaround Leadership for Sustainability in Higher Education : Dean and Department Head Resource Booklet. - Scott, Geoff; Tilbury, Daniella; Sharp, Leith; Deane, Elizabeth (Office for Learning and Teaching, 2012)
Universities play a central role in addressing key challenges of social, economic and environmental sustainability. For this role to be delivered effectively it is critical to identify not only what strategies are most productive but also how to ensure they are successfully led and implemented. This is a resource for deans and department heads, produced as part of a project that sought to apply the proven change leadership framework developed in the ALTC's 'Learning Leaders in Times of Change' project to the distinctive area of effective turnaround leadership for sustainability in higher education. The project was undertaken in a collaboration between the University of Western Sydney, the Australian National University, the Sustainable Futures Academy and the University of Gloucestershire. It produced a validated change leadership framework for building Education for Sustainability (EfS) successfully into the core activities of our universities, as well as a package of leadership development resources for use in individual recruitment, promotion, development and performance management activities. It also documented a range of successful practice models.